Investigation of Ottoman Safavid Manuscripts in TSMK in Terms of Illumination Art through Two Examples - ZOR, Züleyha (MAS Journal of Applied Sciences, 2023)
The art of illumination emerged and developed in the time of Uyghur Turks in Central Asia. This art, which is influenced by China in the east, extending from Uighur geography to Iran, and reaching to Anatolia through the Seljuks, was kneaded with the pleasure of Ottoman art and continued its existence until day. A long centuries in this process, the artists of different geographies have continued to develop by showing their desires to avoid from each other, to express themselves and to be in new quests, aesthetic anxiety, the effects of taste and stylistic differences. Yavuz Sultan Selim conquered Tabriz in Çaldıran Victory in 1514 and brought a lot of Horasan and Tebrizli Nakkaş, who worked in the palace of Shah Ismail, to Istanbul, in the first quarter of the 16th century, these craftsmen who worked together in the Ottoman nakkshahnane, blended the existing styles and adorned exotic artifacts. The interaction between the Safavid period ornamentations and the Ottoman illumination art in the previous century will witness significant changes in both cultures. Therefore, we would later call it the Ottoman Classical period, the art of Turkish illumination has gained a peculiar identity in this period as well as shed light on the future of book arts.In this study, the similarities and differences of the two manuscripts prepared in the Ottoman palace Istanbul nakkaşhane and Safevi-Shiraz in the 16th century will be evaluated in terms of color and composition.